How Does Uncertainty in Economic Policy React to Oil Price Shocks in Australia? - Gregory, Paul R.; Kuang, Kuangli (Journal of Accounting, Business and Finance Research, 2020)
After the financial crisis and during the recession, the concept of economic policy uncertainty (EPU) received a significant amount of attention from researchers and policymakers. The variations in the uncertainties of such policies have been found to have a strong impact on certain economic factors, such as investments and inflation. Investors are most affected by this uncertainty, as they have no clear idea how their investment decisions will impact the economy. In light of this, the researcher has designed this study to explore and analyze the impact of oil price shocks (OPS) in Australia on EPU. Two categories of OPS have been taken into account: oil supply shocks (OSS) and oil shocks (OS) as a result of global demand (GD). The data collected in this study is a time series that covers a period of 28 years in total. Following the data collection, the researcher applied different techniques and tests—the most important of which was a Vector Auto Regression (VAR) model. The results of the current study, which were obtained through the application of a VAR model, indicate that the impact of OPS on EPU varies depending on the time period. In the short-term, the impact is positive; however, in the medium-term, the impact becomes negative and, in the long-term, this impact becomes positive and significant again